The effect of pre-sowing treatment biological preparations of common bean seeds for their sowing qualities - S. V. Zharkova; A. S. Filippova (Овощи России)
Relevance. The use of biological preparations in agricultural technology of agricultural crops contributes to the preservation of agrophytocenosis, reduces environmental pollution and has a positive effect on the growth and development of the plants themselves. In this regard, the determination of the effectiveness of the use of biological products in the presowing treatment of common bean seeds is relevant and timely.Materials and methods. In our study, we studied the effect of presowing treatment of common bean seeds with biological products: Polydon Bio Profi, Polydon Amino Mix, Polydon Aminomix, Alfastim on germination energy, germination, seed sprout size, number of roots and length of the root system. Three varieties were taken as objects of study: Athlete, Omichka, Sirenevaya.Results. A different effect of preparations on the time of seed germination was revealed. The average germination time in options 1-4 was higher than the control values for all varieties, i.e. drugs slowed down germination. The seeds of the tested varieties responded positively to treatment with Alfastim (option 5): the average germination time in Fizkulturnitsa and Sirenevaya decreased by 8.5 and 9.8%, in the Omichka variety by 45%, compared with the control. Among the tested varieties, it is necessary to single out the Sirenevaya variety, which has the highest germination energy (ES) from 90% to 100% and seed germination (VS) from 98-100% in all treatment options. The most effective treatment of the Omichka variety was in option 2 (EP-90%, germination rate 90%), the values exceeded the control by 5%. For all options, the germination energy of the Fizkulturnitsa variety ranged from 72 to 90%, germination from 73 to 93%. A positive effect of drugs on the germination of seeds of this variety was established. The defeat of bean seeds by mold fungi was noted. Seed damage is mild to moderate. Seed damage by mold fungi in the variants using Polydon Bio Profi was absent, or it was weak up to 3.3% for all tested varieties. Morphobiometric indicators of seedlings and their root system in all varieties developed more effectively on variants with the use of Polydon Bio Profi and Alfastim preparations, and their mixtures